Вдосконалення технології управління персоналом на машинобудівних підприємствах - Сочинська-Сибірцева, І. М.; Sochynska-Sybirtseva, I. (My University, 2013)
Розглянуто сутність поняття „технологія управління персоналом”, окреслено основні характеристики технологій управління, відокремлено складові елементи технології в умовах діяльності машинобудівних підприємств, визначено показники кластеризації машинобудівних підприємств з метою вибору напрямку вдосконалення технології управління персоналом. The essence of the concept „technology of human resource management” is considered, the main characteristics of technologies of management are described, making elements of technology in the conditions of activity of machine-building enterprises are allocated, indicators of a clustering of machine-building enterprises for the purpose of a choice of the direction of improvement of technology of human resource management are defined.
The Improvement of Technology of Human Resource Management at Machine-building Enterprises
Keywords: технологія управління; креативність; управління персоналом; кластеризація; technology of management; creativity; human resource management; clustering